Digital Image Correlation As Deformation Measurement Tool In Plastic Film Blowing Process_ - Muniandy, Komethi (2021)
The present research work investigates the use of digital image correlation (DIC) as a potential tool to measure deformation (displacement and strain) during film blowing process which can establish fundamental understanding on relationship between the structure development and film’s properties. Therefore, a feasibility study of DIC method in terms of the surface patterning, validation of the method and selection of DIC parameters were investigated. The comprehensive deformation was assessed using DIC for the bubble formed exiting the die to beyond the freeze line height (FLH) and the corresponding structural development was evaluated using x-ray diffraction (XRD). The progression in deformation and the structural changes as a function of blow up ratio (BUR) and take up ratio (TUR) were studied. Thermal shrinkage study was conducted to investigate the orientation of amorphous polymer molecular structures. In addition, a comprehensive in-plane shrinkage deformation was studied using DIC to understand the response of film towards heat that could visualize the level of deformation available in the produced film. Lastly, the combination effect of the film strain and molecular structure on the mechanical properties was investigated. The DIC was proven to be a reliable method as the results obtained with the ink procedure were comparable to the conventional grid method. For the DIC parameters, subset size of 11 pixels and 21 pixels were preferred for small and large pattern, respectively with subset space of 1 pixel and strain radius of 5 pixels was chosen. The bubble formation during film blowing process can be classified into three regions; initial parison, bubble expansion and beyond freeze line height. The effect of BUR and TUR showed that the films deformed progressively with the stretch ratios. The deformation values increase with stretching ratios except for deformation at transverse direction (TD) which caused by TUR variation. The stretch ratios caused minimal changes on film structure; the crystallinity, interplanar distance (dhkl) and long period slightly reduced upon stretching ratios. The shrinkage strain and shrinkage rate found to be higher with shorter dwell time at higher temperature and stretch ratios. Higher shrinkage strain proves the presence of greater amount of oriented amorphous region. The comparison between conventional and DIC shrinkage measurement showed a satisfactory result confirming DIC can be useful method for comprehensive thermal deformation study. The tensile strength and tensile modulus in machine direction (MD) and TD improved with BUR. For TUR, the properties increased in MD and reduced for TD beyond TUR 1.5. Overall, the tensile strength and tensile modulus was higher in MD than TD. The correlation showed these properties increased linearly with the film strain. A decrease in elongation at break were detected for BUR and TUR. The elongation at break in MD was lower than the elongation at break in TD. There was no linear correlation could be deduced between film strain and elongation at break. Overall, it can be concluded that DIC can be utilized as a suitable tool to measure the deformation (displacement and strain) in plastics film blowing process.